Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s00198-017-3937-z
|View full text |Cite
|
Sign up to set email alerts
|

Validity of height loss as a predictor for prevalent vertebral fractures, low bone mineral density, and vitamin D deficiency

Abstract: This study demonstrated that prospective height loss is an effective tool to identify patients with vertebral fractures, low bone mineral density, and vitamin D deficiency although a lack of height loss does not rule out these diagnoses. If significant height loss is present, the high positive likelihood ratios support a further workup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 24 publications
6
29
0
2
Order By: Relevance
“…Height loss is an age-related physical change that occurs in all individuals over 50 years and that elderly people are aware of [10], and is correlated with osteoporosis [11,12], vertebral fracture [13][14][15][16], and mortality [17]. Decreased QOL is also reportedly associated with height loss according to the EQ-5D scores [18].…”
Section: Introductionmentioning
confidence: 99%
“…Height loss is an age-related physical change that occurs in all individuals over 50 years and that elderly people are aware of [10], and is correlated with osteoporosis [11,12], vertebral fracture [13][14][15][16], and mortality [17]. Decreased QOL is also reportedly associated with height loss according to the EQ-5D scores [18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the proportion of individuals with GNRI <92 was significantly higher in the fracture group than in the non‐fracture group. Also, it has been reported that malnutrition increases the risk of fracture . As is evident from the above, increased anticholinergic load reduces the amount of salivary secretion, causing mouth dryness, and thereby resulting in reduced food intake and drug‐induced malnutrition, which are believed to be associated with the onset of hip fracture.…”
Section: Discussionmentioning
confidence: 98%
“…Also, it has been reported that malnutrition increases the risk of fracture. 23 As is evident from the above, increased anticholinergic load reduces the amount of salivary secretion, causing mouth dryness, and thereby resulting in reduced food intake and drug-induced malnutrition, which are believed to be associated with the onset of hip fracture. Therefore, in patients who are administered anticholinergic drugs, the options of dose reduction or termination should be examined.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research found that vertebral height loss was an important sign of LVF. Mikula et al 36 reported that gradual height loss is a useful measurement tool to identify patients with LVF. Other prospective research, conducted by Moayyeri et al, 37 found that height loss was an important independent risk factor of future LVF at any site (.2 cm over a period of 4 years).…”
Section: Discussionmentioning
confidence: 99%